PDX Journeys Studying and Living in the US, Low-Intermediate Novel and Textbook for University ESL Students - Calderón, Amber Bliss (Open textbook library., 2016)
Each unit begins with a chapter of fiction about a teacher and students in one ESL class. Reading comprehension and reading skills exercises follow. Prefix and suffix vocabulary-focus exercises are included. Academic Word List vocabulary exercises help students build a strong foundation in both receptive and productive knowledge. The following chapters in each unit expand on unit themes through non-fiction articles focusing on academic preparation, international experiences, and cultural adjustment. Vocabulary is repeated and comprehension and reading skills are further practiced.